Influence of the Type and Source of Inoculum on the Start-Up of Anammox Sequencing Batch Reactors (Sbrs) - Montalvo-Martinez, S (TAYLOR & FRANCIS INC, 2013)
Anammox (anaerobic ammonium oxidation) is an attractive option for the treatment of wastewaters with a low carbon/nitrogen ratio. This is due to its low operating costs when compared to the classical nitrification-denitrification processes. However, one of the main disadvantages of the Anammox process is slow biomass growth, meaning a relatively slow reactor start-up. This becomes even more complicated when Anammox microorganisms are not present in the inoculum. Four inocula were studied for the start-up of Anammox sequencing batch reactors (SBRs) 2 L in volume agitated at 100rpm, one of them using zeolite as a microbial support. Two inocula were taken from UASB reactors and two from aerobic reactors (activated sludge and SBR). The Anammox SBRs studied were operated at 36 +/- 0.5 degrees C. The results showed that the only inoculum that enabled the enrichment of the Anammox biomass came from an activated sludge plant treating wastewaters from a poultry slaughterhouse. This plant was designed for organic matter degradation and nitrogen removal (nitrification). This could explain the presence of Anammox microorganisms. This SBR operated without zeolite and achieved nitrite and ammonium removals of 96.3% and 68.4% respectively, at a nitrogen loading rate (NLR) of 0.1kg N/m(3)/d in both cases. The lower ammonium removal was due to the fact that a sub-stoichiometric amount of nitrite (1 molar ratio) was fed. The specific Anammox activity (SAA) achieved was 0.18g N/g VSS/d.